2022
DOI: 10.1371/journal.pone.0268345
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the egg microbiota of the loggerhead sea turtle Caretta caretta in nesting beaches of the Mediterranean Sea

Abstract: Microbes have central roles in the development and health of animals, being the introduction of specific microbial species a potential conservation strategy to protect animals from emerging diseases. Thus, insight into the microbiota of the species and their habitats is essential. In this manuscript, we report for the first time the bacterial composition of all the components (eggshells of hatched and unhatched eggs, internal content of unhatched eggs, intestinal content of hatchling and pipping sea turtles, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
1
8
1
Order By: Relevance
“…Bacteria belonging to other phyla (such as Fusobacteria, Acidobacteria, Chloroflexi) were minor components and were not present in all samples. To the best of our knowledge, only one study has been carried out on the microbiota of sea turtle eggs of the species C. caretta which is mainly dominated by Proteobacteria, Actinobacteria, Firmicutes, Bacteroidetes, and Verrucomicrobia [ 24 ], as we found in our study with differences in the percentages of the phyla. The heat map of the bacterial families (Fig.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Bacteria belonging to other phyla (such as Fusobacteria, Acidobacteria, Chloroflexi) were minor components and were not present in all samples. To the best of our knowledge, only one study has been carried out on the microbiota of sea turtle eggs of the species C. caretta which is mainly dominated by Proteobacteria, Actinobacteria, Firmicutes, Bacteroidetes, and Verrucomicrobia [ 24 ], as we found in our study with differences in the percentages of the phyla. The heat map of the bacterial families (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…In recent years, studies on microbial communities by next-generation sequencing (NGS) of 16S rRNA gene have been applied to the study of the cloacal, oral, intestinal, and skin microbiota of C. caretta sea turtles in the Mediterranean Sea [ 19 – 23 ]. Regarding nest microbiota, only a study has been carried out by analyzing metagenomic DNA [ 24 ], and it was suggested that the maternal and environmental influence alongside a protective role of eggshells shape the egg microbiota of C. caretta sea turtles, as found in other turtles [ 25 , 26 ]. In the summer of 2020, two C. caretta ’s nests located at the beach of Guitgia (Lampedusa, Italy) featured different hatching success rates (0% for nest 1 and 58.90% for nest 2).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, bacterial colonization during egg formation has been suggested in Eastern Fence Lizard ( Sceloporus undulatus ) (Trevelline et al, 2018), and female Sceloporus virgatus lizards transfer beneficial microbes from their cloaca onto their eggs during oviposition with beneficial effects on the offspring (Bunker et al, 2021). Moreover, hatchling loggerhead sea turtles Caretta caretta harboured distinct microbial communities with respect to sand and eggshells, suggesting here also a maternal origin of their pioneer gut microbiome (Vecchioni et al, 2022). In addition, the faecal microbiome of neonate Rock pigeons ( Columba livia ) hatched in an incubator resembled the cloacal microbiome of females sampled from the same population (Dietz et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Their results found that sand microbial composition corresponds to particular environmental conditions suggesting that the presence of pathogenic microbes alone cannot fully determine hatching success (Bézy et al, 2020 ). Vecchioni et al ( 2022 ) used HTS to characterize and compare loggerhead sea turtle egg microbiota along the Italian coasts of the Mediterranean Sea. Their results suggested that egg microbiota are shaped by maternal and environmental influences alongside a protective role of eggshells, but their study lacked microbial sampling from the nesting females to validate this claim (Vecchioni et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vecchioni et al ( 2022 ) used HTS to characterize and compare loggerhead sea turtle egg microbiota along the Italian coasts of the Mediterranean Sea. Their results suggested that egg microbiota are shaped by maternal and environmental influences alongside a protective role of eggshells, but their study lacked microbial sampling from the nesting females to validate this claim (Vecchioni et al, 2022 ). Capri et al ( 2023 ) used HTS and culture‐dependent methods to determine the bacteria and fungi responsible for hatching failure in two green sea turtle nests with different hatching success rates (0% and 59%).…”
Section: Introductionmentioning
confidence: 99%